Effect of High Trace Element Levels in Serum of Women Undergoing Intra-cytoplasmic Sperm Injection (ICSI) on Implantation Rate (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objectives: To assess the effects of trace element concentrations in serum on implantation rate in women undergoing ICSI. Study design: Across-sectional study was conducted between March 2018 to April 2019 in Kamal ALSamarai Hospital, center of fertility and IVF. One hundred and seventeen women underwent ICSI using GnRH-antagonist protocol were recruited. Concentration E2, P4 and two trace elements (Cu, Zn, and Cu/ Zn) were measured in serum specimen. Women’s were evaluated in two groups; the study group consisted of patients with successful implantation (n = 21) and women in the second group (n=96) experienced implantation failure. Results: No significant differences were observed in age or BMI between the groups. Serum copper levels were significantly higher differences (P=0.001) in group of failure (198 ± 107?g/dL) than in group of successful implantation (133 ± 46?g/dL), zinc concentrations in group of successful and failure out of the maximum of normal range (137 ± 40?g/dL versus 135 ± 34?g/ dL respectively) but statistically significant differences were did not observed (P?0.05). When we calculated the copper/zinc ratio (Cu/Zn), it was significantly higher differences (P=0.001) in group of failure (1.59 ± 1) than in group of successful (1.03 ± 0.4). In conclusion, we observed that high serum copper concentrations and (high Cu/Zn ratio) are a risk factor for implantation failure.
Keywords: Implantation failure .Copper. Zinc. Intra-cytoplasmic Sperm Injection.